I want to be a wall. 3 - Shirono, Honami (I want to be a wall, 2024)
Any exciting love story has its fair share of misunderstandings and drama but what is a person to do when they're unable to tell the truth? As an asexual woman and gay man, Yuriko and Gakurouta are keenly aware that their relationship is rather different from what is considered "normal." So when confronted with their families', friends', and society's expectations, they struggle to convey the nature of their marriage. Will the newlyweds be able to hold their ground and find their own version of happily ever after? --from Amazon.